Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Keuangan Daerah: (Studi Empiris pada Satuan Kerja Perangkat Daerah Provinsi Jawa Tengah) - Mudjiyono Mudjiyono (Jurnal Bingkai Ekonomi (JBE), 2019)
The government is required to make financial reports that are useful for users of external and internal financial statements. The prepared report must be comprehensive as a form of accountability that will be examined by the Supreme Audit Agency (BPK). The results of previous studies related to the effect of the presentation of regional financial statements and the accessibility of financial statements to the accountability of regional financial management showed diverse capabilities among regions. Most of the regional governments obtain a percentage below 50%, which means that the presentation of regional financial statements and accessibility of financial statements is less able to express accountability in regional financial management. This has become a problem for some local governments because the systems and reporting that have been there have not been conducive in this direction.Samples that met the requirements were 51 respondents who were executors of financial management directly at the Regional Work Unit of the Central Java Provincial Government. The sampling technique in this study used purposive sampling. The analytical tool used is multiple linear regression analysis. The test results show empirical evidence that: 1. The presentation of financial statements significantly influences the accountability of regional financial management. 2. Accessibility of regional financial reports does not significantly influence the accountability of regional financial management. 3. Accounting information systems significantly influence the accountability of regional financial management.